Preparation method of high-performance alumina fiber reinforced ceramic matrix composite material

By using magnesium aluminum spinel water-based sol and advanced process methods, the problem of degradation of mechanical properties of alumina fiber ceramic matrix composite materials in high temperature environments is solved, and the high performance and environmentally friendly production of materials in extreme environments is achieved.

CN119797904AActive Publication Date: 2025-04-11HUBEI NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411946402.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing alumina fiber reinforced ceramic matrix composite materials have decreased mechanical properties in high temperature environments, the wave transmissive performance and chemical stability of aerogel technology in extreme environments are insufficient, and the preparation process is complicated and not environmentally friendly.

Method used

The new magnesium aluminum spinel aqueous sol is used as the precursor to remove the organic solvent by rotary evaporation to form a stable aqueous sol, combined with the prepreg stack hot pressing and vacuum-assisted impregnation process, reduce the sintering temperature, improve the density of the material and the bonding force between layers.

Benefits of technology

It significantly improves the mechanical strength, durability and wave transmittance of alumina fiber ceramic matrix composite materials, is suitable for applications in ultra-high temperature and extreme environments, and has environmentally friendly processes and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797904A_ABST
    Figure CN119797904A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance alumina fiber reinforced ceramic-based composite material, which comprises the following steps: preparing an alumina fiber fabric, preparing magnesium aluminate spinel aqueous sol, and preparing the composite material: brushing the alumina fiber fabric with the magnesium aluminate spinel aqueous sol for surface drying, laminating and hot-pressing prepreg, and drying to obtain the high-performance alumina fiber reinforced ceramic-based composite material. And sintering in a muffle furnace, cooling to 25 DEG C to obtain an initial alumina fiber ceramic composite material, putting the alumina fiber ceramic composite material into a vacuum-assisted impregnation device for vacuum-assisted impregnation, then putting the alumina fiber ceramic composite material into a drying oven for drying, and repeating the steps of sintering, vacuum-assisted impregnation and drying to obtain the alumina fiber ceramic composite material. And finally, sintering again to obtain the final alumina fiber ceramic-based composite material. The prepared composite material is good in wave-transparent performance, high in mechanical performance, suitable for being used in extreme environments such as ultrahigh temperature and supersonic speed, high in surface flatness and suitable for secondary processing, and large-size and environment-friendly construction can be constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of ceramic-based composite materials, and specifically relates to a method for preparing a high-performance alumina fiber-reinforced ceramic-based composite material. Background Art

[0002] Ceramic Matrix Composites (CMCs) combine the high temperature stability and wave transparency of ceramic materials, and significantly improve the mechanical strength and toughness of the materials by introducing reinforcements such as fibers or particles. Such materials are particularly important in high-end industrial applications that need to withstand extreme temperatures and chemical environments, especially in the aerospace, energy, automotive and military fields, and can provide performance beyond traditional ceramics.

[0003] Magnesium aluminum spinel (MgAl2O4) is a highly heat-resistant ceramic material known for its cubic crystal structure, which contributes to its many excellent physical and chemical properties. With a high melting point (about 2100°C) and good thermal stability, magnesium aluminum spinel performs well in high-temperature applications and can maintain stable physical and chemical properties in high-temperature environments for a long time. The thermal shock resistance of this material makes it less likely to crack when subjected to rapid temperature changes, making it ideal for applications such as aerospace, furnace windows, and high-temperature furnace linings. Magnesium aluminum spinel is very chemically inert and can remain stable even in aggressive chemical environments. It does not react easily with most acids and bases. This makes it an ideal material choice for chemical processing and high-temperature corrosive environments. In the field of electronics and communications, magnesium aluminum spinel has unique advantages in the manufacture of microwave-transparent and isolating devices due to its low dielectric constant and low dielectric loss. In addition, its transparency also makes it useful in the manufacture of certain optical devices, such as windows and lenses at high temperatures, especially in applications that require materials with high transmittance in the infrared and ultraviolet ranges.

[0004] Alumina continuous fiber (ALC) is an excellent composite component, known for its high tensile strength and low volume saturation weight ratio. It usually exists in the form of continuous fibers, which provides better mechanical properties and corrosion resistance than carbon fiber materials. This fiber has an amorphous structure with very few internal voids, making it an ideal choice for manufacturing efficient thermosetting composites. In addition to its excellent mechanical properties and corrosion resistance, ALC also exhibits excellent high temperature resistance and can maintain structural and functional stability in extreme high temperature environments of 1000 to 1200°C. In addition, alumina fibers also have good wave transmission properties, which are particularly suitable for high temperature wave transmission applications, such as high temperature sensors and communication equipment. These characteristics make ALC widely used in aviation, military, automotive manufacturing and other industries, showing a wide range of application potential.

[0005] There are also methods for preparing composite materials with different synthesis processes. CN107805064A relates to a method for preparing an alumina fiber reinforced alumina ceramic matrix composite material, which adopts prepreg molding technology, and realizes the preparation of the composite material by impregnating alumina fibers in alumina slurry, compression molding and high-temperature sintering. CN117682883A describes a method for preparing a fiber-reinforced high-temperature resistant magnesium aluminum spinel aerogel, which prepares magnesium aluminum spinel sol by sol-gel technology, and composites the fiber felt with the sol by impregnation, followed by aging, drying and heat treatment to obtain the final product.

[0006] However, these existing technologies still have certain limitations. The high-temperature sintering process of an alumina fiber reinforced alumina ceramic matrix composite material may damage the microstructure of the material. Especially for alumina fiber materials, high temperature environments will cause their mechanical properties to decrease rapidly, thus affecting the performance of the material in extreme high temperature environments. Aerogel technology improves the thermal insulation performance of the material, but its wave transmission performance and chemical stability under ultra-high temperature and extreme dynamic environments (such as supersonic conditions) need to be enhanced. In addition, aerogels need to be dried using supercritical fluids and other technologies during the preparation process. The equipment cost is high, time-consuming, and the operation is complicated. A large amount of organic solvents are required for aging, and the production process is not environmentally friendly. Moreover, this material is mainly used for industrial kiln insulation structures, so the mechanical properties of composite materials are required to be low. Summary of the invention

[0007] In view of this, the present invention proposes a method for preparing a high-performance alumina fiber reinforced ceramic-based composite material, by utilizing a new type of magnesium aluminum spinel aqueous sol as a precursor, and ultimately reducing the sintering temperature of the composite material molding to obtain an alumina fiber reinforced magnesium aluminum spinel ceramic-based composite material.

[0008] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material comprises the following steps: 1) Preparing an alumina fiber fabric: preparing continuous alumina fibers and weaving them into an alumina fiber fabric, and washing the alumina fiber fabric with an organic solvent; 2) preparing an aqueous sol of magnesium-aluminum spinel: dissolving a magnesium source and an aluminum source in an organic solvent at the same time, stirring evenly, the stirring time is 10-60 minutes, and adjusting the pH value to 9-10 with aqueous ammonia, forming a transparent sol solution by controlled hydrolysis, placing the sol solution in a flask, and loading it into a rotary evaporator, the temperature of the rotary evaporator is set at 40-60° C., and the rotation rate is set at 40-60 r / min. After removing the organic solvent by rotary evaporation, deionized water is added at 20% of the volume of the organic solvent to obtain a stable aqueous sol of magnesium-aluminum spinel; 3) Preparation of composite materials: After the magnesium aluminum spinel aqueous sol is brushed on the alumina fiber fabric and dried, the prepreg stack is hot-pressed and then sintered in a muffle furnace at a temperature of 700-900°C for 1-3 hours. After cooling to 25°C, the initial alumina fiber ceramic composite material is obtained. The alumina fiber ceramic composite material is placed in a vacuum-assisted impregnation device for vacuum-assisted impregnation. After the impregnation is completed, the vacuum-assisted impregnation device containing the alumina fiber ceramic composite material is placed in an oven for drying. The sintering-vacuum-assisted impregnation-drying steps are repeated, and finally sintered again to obtain the final alumina fiber ceramic-based composite material.

[0009] Furthermore, the structure of the alumina fiber fabric woven in step 1) is a two-dimensional stacked structure, and the fiber volume content of the fabric is (45±2)%.

[0010] Furthermore, the cleaning method of the organic solvent in step 1) is: using acetone to clean by ultrasonic assistance for 10 minutes, and the cleaning is repeated 3 to 5 times.

[0011] Furthermore, the magnesium source in step 2) is one or more combinations of magnesium acetate, magnesium ethoxide, anhydrous magnesium chloride, magnesium chloride hexahydrate, magnesium acetate tetrahydrate, and magnesium sulfate, and the aluminum source is one or more combinations of aluminum isopropoxide, anhydrous aluminum chloride, aluminum chloride hexahydrate, aluminum nitrate hexahydrate, aluminum hydroxide, and aluminum sec-butoxide.

[0012] Furthermore, the organic solvent in step 2) is one or more combinations of anhydrous methanol, anhydrous ethanol, n-propanol, isopropanol, N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMA).

[0013] Furthermore, in step 2), the molar ratio of the magnesium source to the aluminum source is 1:1.8-2.2, and the mass ratio of the total mass of the magnesium source and the aluminum source to the organic solvent is 1:60-100.

[0014] Furthermore, in step 3), the pressure applied by vacuum-assisted impregnation is 3 to 7 MPa, and the pressure holding time at 25° C. is 24 to 96 hours.

[0015] Furthermore, in step 3), the temperature of the oven drying is 100-140° C., and the drying time is 24-72 hours.

[0016] Furthermore, in step 3), the sintering-vacuum assisted impregnation-drying steps are repeated 3 to 7 times.

[0017] The beneficial effects of the present invention are as follows: (1) The present invention ensures the uniformity of the reaction and the appropriate concentration of the solution by precisely controlling the appropriate magnesium-aluminum molar ratio and the volume of the solvent, thereby forming a uniform precursor sol. The rotary evaporation temperature and the rotation rate are controlled to make the solvent evaporate evenly, prevent overheating and decomposition, and improve production efficiency. The aqueous sol usually has good dispersibility, which can ensure the uniformity of the material in the subsequent molding and sintering process. The aqueous sol is environmentally friendly and does not release harmful gases during the molding process. It is green and environmentally friendly and more conducive to large-scale production. Using the prepreg lamination hot pressing process, multiple layers of fiber cloth coated with sol are stacked and preformed by a hot pressing process to form a prepreg blank. By slowly raising the temperature, the growth process of the grains is controlled to prevent excessive grain growth and the formation of crystal defects, while ensuring uniform sintering and uniform particle size. Subsequently, the vacuum-assisted impregnation process is used to fully penetrate the aqueous magnesium-aluminum spinel sol in a vacuum environment, thereby significantly improving the density and interlayer bonding strength of the alumina fiber ceramic matrix composite material. This method effectively fills the pores and tiny cracks inside the material, reduces defects and improves the mechanical strength and durability of the material. Ultimately, vacuum-assisted impregnation ensures the high performance of the composite material, making it more suitable for applications in high temperatures and extreme environments. The lower sintering temperature optimizes the crystal structure and particle size distribution of the magnesium-aluminum spinel, improves the purity, hardness, transparency and mechanical properties of the material, while also reducing the damage to the alumina fiber caused by thermal stress caused by repeated sintering processes. Therefore, the present invention not only improves the quality and performance of the composite material, but also reduces production costs and improves the controllability and consistency of the process, making this method have significant advantages in large-scale production and industrial applications; (2) The composite material prepared by the present invention has good wave transmission performance and strong mechanical properties, and is suitable for use in extreme environments such as ultra-high temperature and supersonic speed. The prepared composite material has high surface flatness and is suitable for secondary processing. It can construct large-scale, environmentally friendly structures. Compared with the prior art, the present invention significantly improves the performance of the material in terms of high-temperature stability, mechanical properties and wave transmission characteristics by introducing a composite structure of magnesium aluminum spinel and alumina fiber. It is particularly suitable for applications in extreme environments, showing significant technical advantages and application potential. Moreover, the magnesium aluminum spinel sol used in the present invention is an aqueous sol, and no organic sol is required in the process of large-scale components, which is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a preparation flow chart of a high-performance alumina fiber ceramic-based composite material.

[0019] Figure 2 This is a photo of the magnesium aluminum spinel aqueous sol precursor obtained in Example 1.

[0020] Figure 3 This is the XRD pattern of the magnesia-alumina spinel ceramic obtained in Example 1.

[0021] Figure 4 This is the XRD pattern of the alumina fiber reinforced ceramic matrix composite material obtained in Example 1.

[0022] Figure 5 This is the SEM image of the alumina fiber reinforced ceramic matrix composite material obtained in Example 1.

[0023] Figure 6 This is the SEM image of the magnesium aluminum spinel in the composite material obtained in Example 1.

[0024] Figure 7 This is the SEM image of the magnesium aluminum spinel ceramic in the composite material obtained in Comparative Example 1.

[0025] Figure 8 This is the SEM image of the magnesium aluminum spinel ceramic in the composite material obtained in Comparative Example 2. DETAILED DESCRIPTION

[0026] In order to more thoroughly understand the features and technical contents of the present invention, the implementation of the present invention is described in detail below in conjunction with the accompanying drawings. The attached drawings are for reference only and are not intended to limit the present invention.

[0027] 1. Implementation Embodiment 1: like Figure 1 As shown, a method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material comprises the following steps: Step 1): preparing alumina fiber fabric: preparing continuous alumina fibers and weaving them into a two-dimensional stacked structure of alumina fiber fabric, the fiber volume content of the fabric is 43%, and the alumina fiber fabric is cleaned with acetone by ultrasound for 10 minutes, and the cleaning is repeated 3 times.

[0028] Step 2): preparing an aqueous sol of magnesium aluminum spinel: 0.1424 g of magnesium acetate, 0.4084 g of aluminum isopropoxide, and 30 ml of n-propanol were mixed and stirred evenly for 10 min, and the pH value was adjusted to 9 to form a transparent sol solution by controlled hydrolysis. The sol solution was placed in a flask and loaded into a rotary evaporator. The temperature of the rotary evaporator was set at 40° C. and the rotation rate was set at 40 r / min. After removing the organic solvent by rotary evaporation, 6 ml of deionized water was added. After adding water, rotary evaporation was continued until the sol state was obtained to obtain a stable aqueous sol of magnesium aluminum spinel; Step 3): Preparation of composite materials: After the magnesium aluminum spinel aqueous sol is brushed on the alumina fiber fabric and dried, the prepreg stack is hot-pressed, and then placed in a muffle furnace for sintering, and the temperature is gradually increased to 800°C at 5°C / min, sintered for 3 hours, and cooled to 25°C to obtain the initial alumina fiber ceramic composite material. The alumina fiber ceramic composite material is vacuum-assisted impregnated and placed in a vacuum-assisted impregnation device. A pressure of 6MPa is applied to the vacuum impregnation device, and the pressure is maintained at 25°C for 72 hours to further promote the impregnation of the precursor; the vacuum impregnation device containing the composite material is transferred to a 120°C oven and dried for 72 hours to perform molding and curing operations on the composite material. The sintering-vacuum-assisted impregnation-drying steps are repeated 5 times, and finally the temperature is gradually increased to 800°C at 5°C / min and sintered for 3 hours to prepare an alumina fiber reinforced magnesium aluminum spinel composite material with excellent performance. Figure 2-Figure 6 As shown, the density of the prepared material is 2.37 g / cm 3 , porosity is 28.9%, flexural strength: 254.90 ± 13.94 MPa.

[0029] Embodiment 2: The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material is the same as that described in Example 1, except that: in step 1), 0.1424 g of magnesium acetate is replaced with 0.114 g of magnesium ethoxide. At the same time, the rotary evaporator temperature in step 2) is replaced from 40 °C to 60 °C. The density of the prepared material is 2.35 g / cm 3 , porosity is 29.1%, flexural strength: 254.91 ± 15.31MPa.

[0030] Embodiment 3: The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material is the same as that described in Example 1, except that: in step (1), 0.4084 g of aluminum isopropoxide is replaced by 0.267 g of anhydrous aluminum chloride, and 30 ml of n-propanol is replaced by n-propanol + DMF (1:1) solution. The density of the prepared material is 2.29 g / cm 3 , porosity is 29.8%, flexural strength: 249.82 ± 14.27MPa.

[0031] Embodiment 4: The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material is the same as that described in Example 1, except that in step 6) of the sintering-vacuum assisted impregnation-drying step, the vacuum assisted impregnation holding time is changed to 24 hours. The composite material density is slightly lower than that of Example 3. The prepared material density is 2.23 g / cm 3 , porosity is 31.4%, flexural strength: 231.54± 13.89 MPa.

[0032] Embodiment 5: Step 1): preparing alumina fiber fabric: preparing continuous alumina fibers and weaving them into a two-dimensional stacked structure of alumina fiber fabric, the fiber volume content of the fabric is 43%, and the alumina fiber fabric is cleaned with acetone by ultrasound for 10 minutes, and the cleaning is repeated 3 times.

[0033] Step 2): preparing an aqueous sol of magnesium aluminum spinel: 0.1424 g of magnesium acetate, 0.3676 g of aluminum isopropoxide, and 30 ml of n-propanol were mixed and stirred evenly for 10 min, and the pH value was adjusted to 9 to form a transparent sol solution by controlled hydrolysis. The sol solution was placed in a flask and loaded into a rotary evaporator. The temperature of the rotary evaporator was set at 40° C. and the rotation rate was set at 40 r / min. After removing the organic solvent by rotary evaporation, 6 ml of water was added. After adding water, rotary evaporation was continued until the sol state was obtained to obtain a stable aqueous sol of magnesium aluminum spinel; Step 3): Preparation of composite materials: After the magnesium aluminum spinel aqueous sol is brushed on the alumina fiber fabric and dried, the prepreg stack is hot pressed, and then placed in a muffle furnace for sintering, the temperature is gradually increased to 700°C at 5°C / min, sintered for 1 hour, and cooled to 25°C to obtain the initial alumina fiber ceramic composite material. The alumina fiber ceramic composite material is vacuum-assisted impregnated and placed in a vacuum-assisted impregnation device. A pressure of 3MPa is applied to the vacuum impregnation device, and the pressure is maintained at 25°C for 24 hours to further promote the impregnation of the precursor; the vacuum impregnation device containing the composite material is transferred to a 100°C oven for drying for 24 hours, and the composite material is formed and cured. The sintering-vacuum-assisted impregnation-drying steps are repeated 3 times, and finally the temperature is gradually increased to 700°C at 5°C / min and sintered for 1 hour to prepare an alumina fiber reinforced magnesium aluminum spinel composite material with excellent performance. The density of the prepared material is 2.13g / cm 3 , porosity is 33.2%, flexural strength: 223.73± 14.52 MPa.

[0034] Embodiment 6: Step 1): preparing alumina fiber fabric: preparing continuous alumina fibers and weaving them into a two-dimensional stacked structure of alumina fiber fabric, the fiber volume content of the fabric is 45%, and using acetone to clean the alumina fiber fabric by ultrasound for 10 minutes, and the cleaning is repeated 4 times.

[0035] Step 2): preparing an aqueous sol of magnesium aluminum spinel: 0.1424 g of magnesium sulfate, 0.4492 g of anhydrous aluminum chloride, and 60 ml of anhydrous methanol were mixed and stirred evenly for 30 min, and the pH value was adjusted to 9.5, and a transparent sol solution was formed by controlled hydrolysis, and the sol solution was placed in a flask and loaded into a rotary evaporator. The temperature of the rotary evaporator was set at 50° C. and the rotation rate was set at 50 r / min. After removing the organic solvent by rotary evaporation, 12 ml of water was added, and after adding water, rotary evaporation was continued until the sol state was obtained to obtain a stable aqueous sol of magnesium aluminum spinel; Step 3): Preparation of composite materials: After the magnesium aluminum spinel aqueous sol is brushed on the alumina fiber fabric and dried, the prepreg stack is hot pressed, and then placed in a muffle furnace for sintering, gradually heating to 800°C at 5°C / min, sintering for 2h, and cooling to 25°C to obtain the initial alumina fiber ceramic composite material, vacuum-assisted impregnation of the alumina fiber ceramic composite material, placed in a vacuum-assisted impregnation device, and a pressure of 5MPa is applied to the vacuum impregnation device, and the pressure is maintained at 25°C for 48h to further promote the impregnation of the precursor; the vacuum impregnation device containing the composite material is transferred to a 120°C oven for drying for 48h, and the composite material is formed and cured. The sintering-vacuum-assisted impregnation-drying steps are repeated 5 times, and finally the temperature is gradually increased to 800°C at 5°C / min and sintered for 2h to prepare an alumina fiber reinforced magnesium aluminum spinel composite material with excellent performance. The density of the prepared material is 2.22g / cm 3 , porosity is 31.3%, flexural strength: 231.25± 13.35 MPa.

[0036] Embodiment 7: Step 1): preparing alumina fiber fabric: preparing continuous alumina fibers and weaving them into a two-dimensional stacked structure of alumina fiber fabric, the fiber volume content of the fabric is 47%, and the alumina fiber fabric is cleaned with acetone by ultrasound for 10 minutes, and the cleaning is repeated 5 times.

[0037] Step 2): preparing an aqueous sol of magnesium aluminum spinel: 0.1424 g of magnesium chloride hexahydrate, 0.4084 g of aluminum chloride hexahydrate, and 44 ml of anhydrous ethanol were mixed and stirred evenly for 60 min, and the pH value was adjusted to 10, and a transparent sol solution was formed by controlled hydrolysis, and the sol solution was placed in a flask and loaded into a rotary evaporator. The temperature of the rotary evaporator was set at 60° C. and the rotation rate was set at 60 r / min. After removing the organic solvent by rotary evaporation, 9 ml of water was added, and after adding water, rotary evaporation was continued until the sol state was obtained to obtain a stable aqueous sol of magnesium aluminum spinel; Step 3): Preparation of composite materials: After the magnesium aluminum spinel aqueous sol is brushed on the alumina fiber fabric and dried, the prepreg stack is hot pressed, and then placed in a muffle furnace for sintering, gradually heating to 900°C at 5°C / min, sintering for 3 hours, and cooling to 25°C to obtain the initial alumina fiber ceramic composite material, vacuum-assisted impregnation of the alumina fiber ceramic composite material, placed in a vacuum-assisted impregnation device, and a pressure of 7MPa is applied to the vacuum impregnation device, and the pressure is maintained at 25°C for 96 hours to further promote the impregnation of the precursor; the vacuum impregnation device containing the composite material is transferred to a 140°C oven for drying for 72 hours, and the composite material is formed and cured. The sintering-vacuum-assisted impregnation-drying steps are repeated 7 times, and finally the temperature is gradually increased to 900°C at 5°C / min and sintered for 3 hours to prepare an alumina fiber reinforced magnesium aluminum spinel composite material with excellent performance. The density of the prepared material is 2.29g / cm 3 , porosity is 29.6%, flexural strength: 212.25± 16.13 MPa.

[0038] 2. Comparison Comparative Example 1: The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material is the same as that described in Example 1, except that the sintering temperature is changed, that is, in step 3), the sintering is changed from gradually increasing the temperature to 800°C at 5°C / min to gradually increasing the temperature to 1200°C at 5°C / min. The density of the prepared material is 2.31 g / cm 3 , porosity is 30.3%, flexural strength: 156.49 MPa.

[0039] like Figure 7 As shown in Figure 2, during high-temperature sintering, alumina fiber-reinforced Mg-alumina spinel composites may experience morphological changes, grain growth, and the generation of defects such as pores and microcracks, which can weaken the mechanical properties of the fiber and the overall performance of the composite. In addition, the accumulation of thermal stress may lead to interfacial microcracks or delamination, further affecting the structural integrity and service life of the material.

[0040] Comparative Example 2: The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material is the same as that described in Example 1, except that: Step 2) a transparent sol solution is formed by controlled hydrolysis, and then the organic solvent is replaced by water, and the organic solvent is directly used to form a gel. The density of the prepared material is 2.36 g / cm 3 , porosity: 27.6%, flexural strength: 101.37 MPa.

[0041] like Figure 8As shown, the process of forming a gel using only organic solvents without adding water may lead to problems such as difficult gelation, incomplete reaction, and unsatisfactory pore structure, which in turn affects the quality and application performance of the final material.

[0042] The specific models of the above-mentioned devices are not limited or described in detail, and the in-depth connection methods of the above-mentioned devices are not described in detail. As common knowledge, technicians in this field can understand it.

[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material, characterized in that: The following steps are involved: 1) Preparing an alumina fiber fabric: preparing continuous alumina fibers and weaving them into an alumina fiber fabric, and washing the alumina fiber fabric with an organic solvent; 2) preparing an aqueous sol of magnesium-aluminum spinel: dissolving a magnesium source and an aluminum source in an organic solvent at the same time, stirring evenly, the stirring time is 10-60 minutes, and adjusting the pH value to 9-10 with aqueous ammonia, forming a transparent sol solution by controlled hydrolysis, placing the sol solution in a flask, and loading it into a rotary evaporator, the temperature of the rotary evaporator is set at 40-60° C., and the rotation rate is set at 40-60 r / min. After removing the organic solvent by rotary evaporation, deionized water is added at 20% of the volume of the organic solvent to obtain a stable aqueous sol of magnesium-aluminum spinel; 3) Preparation of composite materials: After the magnesium aluminum spinel aqueous sol is brushed on the alumina fiber fabric and dried, the prepreg stack is hot-pressed and then sintered in a muffle furnace at a temperature of 700-900°C for 1-3 hours. After cooling to 25°C, the initial alumina fiber ceramic composite material is obtained. The alumina fiber ceramic composite material is placed in a vacuum-assisted impregnation device for vacuum-assisted impregnation. After the impregnation is completed, the vacuum-assisted impregnation device containing the alumina fiber ceramic composite material is placed in an oven for drying. The sintering-vacuum-assisted impregnation-drying steps are repeated, and finally sintered again to obtain the final alumina fiber ceramic-based composite material.

2. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The structure of the alumina fiber fabric woven in step 1) is a two-dimensional stacked structure, and the fiber volume content of the fabric is (45±2)%.

3. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 2, characterized in that: The cleaning method of the organic solvent in step 1) is: using acetone to clean with ultrasound for 10 minutes, and repeating the cleaning 3 to 5 times.

4. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 3, characterized in that: The magnesium source in step 2) is one or more combinations of magnesium acetate, magnesium ethoxide, anhydrous magnesium chloride, magnesium chloride hexahydrate, magnesium acetate tetrahydrate, and magnesium sulfate; the aluminum source is one or more combinations of aluminum isopropoxide, anhydrous aluminum chloride, aluminum chloride hexahydrate, aluminum nitrate hexahydrate, aluminum hydroxide, and aluminum sec-butoxide.

5. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 4, characterized in that: The organic solvent in step 2) is one or more combinations of anhydrous methanol, anhydrous ethanol, n-propanol, isopropanol, N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMA).

6. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 5, characterized in that: Step 2) The molar ratio of the magnesium source to the aluminum source is 1:1.8-2.2, and the mass ratio of the total mass of the magnesium source and the aluminum source to the organic solvent is 1:60-100.

7. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 6, characterized in that: In step 3), the pressure applied by vacuum-assisted impregnation is 3 to 7 MPa, and the pressure holding time is 24 to 96 hours at 25°C.

8. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 7, characterized in that: Step 3) The temperature of drying in an oven is 100 to 140° C. and the drying time is 24 to 72 hours.

9. The method for preparing a high-performance alumina fiber reinforced ceramic matrix composite material according to claim 8, characterized in that: Step 3) Repeat the sintering-vacuum assisted impregnation-drying steps 3 to 7 times.

Citation Information

Patent Citations

  • Preparation method of alumina fiber reinforced alumina ceramic-based composite material by using prepreg forming method

    CN117682883A

  • Method for preparing fiber-reinforced high-temperature-resistant magnesium aluminum spinel aerogel

    CN107805064A

  • Preparation method of alumina fiber reinforced ceramic composite material containing alumina interface layer

    CN112250460A

  • Preparation method of alumina fiber reinforced ceramic composite material containing mullite interface layer

    CN114455961A

  • Spinel structure high-temperature-resistant aerogel thermal insulation material and preparation method thereof

    CN118894732A